Main mechanisms for stimulating reserves for industrial production growth - Muxamedjanovna, Yakubova Dildar (Goodwood Publishing, 2025)
Purpose: This study discusses how to stimulate and improve medium- and long-term reserves for the growth of gross industrial production in Uzbekistan. It highlights the factors that influence the formation of industrial development reserves, including labor productivity, utilization of production capacity, and modernization of fixed assets. Method: This study applies a methodology that integrates strategic planning with a structured evaluation model to support national innovation development. By systematically analyzing production and economic activities, it identifies the interrelated elements and conditions that contribute to industrial reserves. Results: The economic analysis revealed significant potential reserves for production growth in industrial enterprises. Through a quantitative assessment of resources and their interconnections, this study shows that labor efficiency, improved use of capacities, and investment in fixed assets are key drivers of sustainable industrial development. Conclusion: Strengthening medium- and long-term reserves is essential for Uzbekistan’s industrial growth. Effective strategies should focus on enhancing productivity, innovation, and optimal use of production systems, aligning industrial management with national innovation policies. Limitation: This study relies mainly on macro-level and generalized enterprise data, which may overlook sectoral or regional differences. The absence of longitudinal analysis also limits the ability to assess the long-term effectiveness of the proposed measures. Contribution: This study contributes to industrial economics by providing a structured framework for identifying, quantifying, and managing production reserves. Practically, it offers policymakers and industry leaders a roadmap for improving efficiency, supporting innovation, and ensuring sustainable industrial expansion in Uzbekistan.